2021
DOI: 10.1111/jfpp.15885
|View full text |Cite
|
Sign up to set email alerts
|

Multiple responses optimization of antioxidative components extracted from distiller's grains using response surface methodology and identify their chemical compositions

Abstract: Baijiu is a traditional alcoholic drink in China, also one of the oldest distillates globally, with more than 2000 years of history from the Western Han dynasty. It is a general term for traditional Chinese liquor except for rice or fruit wines. Baijiu is fermented from rice, wheat, sorghum, and corn grains (Zheng & Han, 2016). Due to Baijiu's taste and unique aroma produced by microorganisms during grain fermentation (Zhang, Zhu, et al., 2017b), Baijiu has a wide range of enthusiasts worldwide, making Baijiu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These carbohydrates endow distiller's grains with energy value and play an important role in food and feed production. Distiller's grains also contain abundant phenolic compounds, such as phenolic acids and flavonoids, which are related to antioxidant effects and are believed to be a source of antioxidant active substances [5][6][7][8] . Phosphorus and potassium in distiller's grains are important components of inorganic fertilizers, while organic substances such as lignin and cellulose starch are combustible and can be used as combustion energy [9,10] .…”
Section: Composition Analysis Of Distiller's Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…These carbohydrates endow distiller's grains with energy value and play an important role in food and feed production. Distiller's grains also contain abundant phenolic compounds, such as phenolic acids and flavonoids, which are related to antioxidant effects and are believed to be a source of antioxidant active substances [5][6][7][8] . Phosphorus and potassium in distiller's grains are important components of inorganic fertilizers, while organic substances such as lignin and cellulose starch are combustible and can be used as combustion energy [9,10] .…”
Section: Composition Analysis Of Distiller's Grainsmentioning
confidence: 99%
“…The solid part contains proteins, insoluble carbohydrates, organic acids, yeast, inorganic salts, and phenolic molecules, while the liquid part is mainly composed of ethanol, acetic acid, and lactic acid. In addition to the main components mentioned above, its polyphenols are diverse and rich in content, possessing certain antioxidant capabilities, making it an ideal raw material for obtaining phenolic compounds [7][8][9] . In our previous research, it was found that the water content of distiller's grains was around 65%, and the total phenolic content reached 2.5mg/g.…”
Section: Composition Analysis Of Distiller's Grainsmentioning
confidence: 99%
“…Distillery lees are the main byproduct of the distillation industry [1,2] and play a key role in the circular economy [3]. China has a 2000-year history of brewing liquor [4] as a major producer and consumer. The annual production of distillery lees is as high as 58.66 million tons [5], ranking first in the world [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Distillery lees have high moisture content and acidity and are prone to corruption during storage. Traditional disposal methods, such as stacking and discarding, cause environmental pollution [4] and resource waste [8,9]. At present, distillery lees are mainly used in the production of protein feed, bio-organic fertilizers, chemical products, production fuel, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reuse of DGS has become an effective way of reducing the environmental pollution risks and costs of Baijiu production, such as preparing new biomass materials from DGS, [3] transforming DGS into animal feed, [4,5] and purifying residual components such as flavonoids, proteins, and polyphenols in DGS. [6][7][8][9] Starch is one of the primary residues in DGS. [10] However, the changes in DGS starch in the Baijiu production and residual starch formation in DGS, and the effects of layered distillation and layered fermentation on residual starch in Baijiu production have not been known.…”
Section: Introductionmentioning
confidence: 99%